Two-dimensional cylindrical magnetosonic shock waves in a relativistic degenerated plasma - Mahmood A H Khaled; Yusra A A Hager; Mohamed A Shukri (New Journal of Physics)
In this paper, the characteristics of two-dimensional magnetosonic (MS) shock waves have been studied in a nonplanar relativistic degenerate collisional magnetoplasma whose constituents are non-degenerate warm ions and relativistic degenerated electrons. Employing fluid model equations for such plasma along with Maxwell equations, a set of magnetohydrodynamic (MHD) model equations is obtained. Based on the newly obtained MHD equations, a Burgers–Kadomstev–Petviashvili (Burger–KP) equation (which describes shock wave structures) is derived in cylindrical geometry using the reductive perturbation technique. The considered plasma system was investigated under the impacts of spin-magnetization, relativistic degeneracy, cylindrical geometry, and dissipation. Numerical results revealed that the relativistic degeneracy, dissipation, and electron spin-magnetization as well as nonplanar geometry significantly altered the MS shock wave properties. Interestingly, it is found that there is a change in the shock nature and emergence of new structures due to the influences of both transverse perturbation and cylindrical geometry. The implications of our investigation may be applicable to dense astrophysical environments, particularly neutron stars, and white dwarfs at which the relativistic degenerated electrons are existed.